2020
DOI: 10.1021/acsami.9b20639
|View full text |Cite
|
Sign up to set email alerts
|

Single-Layered Graphene/Au-Nanoparticles-Based Love Wave Biosensor for Highly Sensitive and Specific Detection of Staphylococcus aureus Gene Sequences

Abstract: In this work, a single-layered graphene (SLG)/Au-nanoparticles (NPs)-based Love wave biosensor was prepared for detection of Staphylococcus aureus (S. aureus) gene sequences. The annealing process was proposed to obtain a larger-area interface with ssDNA. The sensitivity was verified by detecting S. aureus gene sequences with a linear detection ranging from 0 to 10 nmol/L, where the limit of detection (LOD) was only 12.4 pg/mL. The stable state of the biosensors based on SLG/Au NPs in the liquid phase could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…(Reproduced with permission from Ref. ( Ji et al, 2020 ). Copyright 2020, American Chemical Society).…”
Section: Graphene Biosensors For Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…(Reproduced with permission from Ref. ( Ji et al, 2020 ). Copyright 2020, American Chemical Society).…”
Section: Graphene Biosensors For Pathogensmentioning
confidence: 99%
“…Recently, Ji and colleagues developed a graphene/AuNPs based Love wave biosensor for the detection of S. aureus gene sequences ( Fig. 1 C) ( Ji et al, 2020 ). Surface acoustic wave (SAW) sensor is a kind of piezoelectric mass sensor, which is sensitive to surface mass loading since the loading has a great influence on the propagation of the acoustic wave ( Ballantine Jr et al, 1996 ).…”
Section: Graphene Biosensors For Pathogensmentioning
confidence: 99%
“…Recently, several works show that the concentration of ssDNAs can actually be quantified, where the concentration is in proportional to the measured phase shift of the SAW. 55,[60][61][62][63] Some of these SAW sensors can detect the mismatch with the resolution of up to single base pair. Such high sensitivity can be achieved by applying GHz SAW as reported by Cai et al, 60 employing silver-nanoparticle amplification technique as reported by Zhang et al 62 and coating the piezoelectric surface with a sensitive layer as reported by Ji et al 61 Sensing the mismatch is important in modern structural DNA nanotechnology where ssDNAs are used to self-assemble complicated structures for different applications, 64 as the mismatch is an indicator of the defect in the DNA-assembled biomaterials.…”
Section: Biomoleculesmentioning
confidence: 99%
“…55,[60][61][62][63] Some of these SAW sensors can detect the mismatch with the resolution of up to single base pair. Such high sensitivity can be achieved by applying GHz SAW as reported by Cai et al, 60 employing silver-nanoparticle amplification technique as reported by Zhang et al 62 and coating the piezoelectric surface with a sensitive layer as reported by Ji et al 61 Sensing the mismatch is important in modern structural DNA nanotechnology where ssDNAs are used to self-assemble complicated structures for different applications, 64 as the mismatch is an indicator of the defect in the DNA-assembled biomaterials. From this perspective, SAW sensors hold great promise to become new characterizing tools for evaluating the quality of the DNA-based biomaterials.…”
Section: Biomoleculesmentioning
confidence: 99%
“…For bacterial infection, surfaces of graphene products, graphite, graphene, graphene oxide and reduced graphene oxide have been revealed to be a good platform for antibacterial effects and improved biocompatibility in tissue engineering, biosensors or antimicrobial agent-carriage [54]. A graphene (SLG)/Au NP-based biosensor has been used in the diagnosis of S. aureus gene sequences, with detection limits as low as 12.4 pg/mL [55]. A biosensor using reduced graphene oxide-carbon nanocomposites prepared using the hydrothermal method has been used for precise and fast label-free electrochemical detection of pathogenic bacteria, such as S. enterica, in a wide linear dynamic range from 10 1 to 10 8 cfu mL −1 and with a 10 1 cfu mL −1 limit of detection [56].…”
Section: Graphene-based Biosensorsmentioning
confidence: 99%